‘Moderate universalism’ in China and the Nordic countries: reviewing the major challenges in unemployment protection - Kristian Kongshøj (Nordic Journal of Social Research)
Rapid welfare expansion is taking place in China across a range of policy fields. In the Nordic countries, intra-Nordic diversity and significant policy changes are not difficult to identify despite the notion of universal Nordic welfare regimes. This article will bridge these very different worlds of welfare in an effort to classify the Chinese unemployment-protection system with a comparative framework aimed at furthering the emerging Sino-Nordic research dialogue. This research dialogue has gained relevance in recent years with the new official Chinese goal of building a more universal welfare system. Welfare research that includes China from a comparative perspective is still extremely rare. Despite the lofty Chinese goals, many Chinese policy challenges still loom large. These are the rural-urban divide exacerbated by the Chinese household registration system, coverage of unemployment insurance and social assistance, inadequate and declining benefit levels, and, finally, funding issues. As this article will also substantiate, Denmark and Finland are something approaching best cases for illustrating intra-Nordic diversity. As regards the Chinese challenges, it is explained how they can to some extent be understood as the teething troubles of a developmental welfare state, since the Nordic counterparts have faced similar issues during their eras of welfare expansion.